2022
DOI: 10.1515/cclm-2022-0239
|View full text |Cite
|
Sign up to set email alerts
|

Patients with severe COVID-19 do not have elevated autoantibodies against common diagnostic autoantigens

Abstract: Objectives Infection by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative pathogen of coronavirus disease 2019 (COVID-19) presents occasionally with an aberrant autoinflammatory response, including the presence of elevated circulating autoantibodies in some individuals. Whether the development of autoantibodies against self-antigens affects COVID-19 outcomes remains unclear. To better understand the prognostic role of autoantibodies in COVID-19, we quantified autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The presence of autoantibodies may predict the adverse clinical course of COVID-19 patients [ 59 ]. However, some studies have also indicated that autoantibodies to any marker tested were not significantly elevated in patients with severe COVID-19, such as anti-IFN antibodies that are unlikely to promote long-term COVID-19 symptoms after the acute phase of infection [ 60 , 61 ]. As for molecular mimicry, it is one of the mechanisms by which a virus can induce an autoimmune response, with the production of specific autoantibodies and the action of certain vaccine adjuvants seem to be important factors in the autoimmune phenomenon [ 53 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of autoantibodies may predict the adverse clinical course of COVID-19 patients [ 59 ]. However, some studies have also indicated that autoantibodies to any marker tested were not significantly elevated in patients with severe COVID-19, such as anti-IFN antibodies that are unlikely to promote long-term COVID-19 symptoms after the acute phase of infection [ 60 , 61 ]. As for molecular mimicry, it is one of the mechanisms by which a virus can induce an autoimmune response, with the production of specific autoantibodies and the action of certain vaccine adjuvants seem to be important factors in the autoimmune phenomenon [ 53 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility and hyperactivation of the host immune system may trigger autoimmune diseases (Esmaeili et al, 2017;Scappaticcio et al, 2021). Similar to patients infected with other viruses, infected with SARS-CoV-2 show altered autoantibody profiles (Zhou Y. et al, 2020;Peker et al, 2021;Scappaticcio et al, 2021b), such as, antinuclear antibodies, antithyroid antibodies, chromatin proteins, ribosomal proteins, and immunerelated proteins (Bastard et al, 2020;Chang et al, 2021;Ulndreaj et al, 2022). These autoantibodies are closely correlated with the disease severity and the prognosis of COVID-19 patients and may trigger long-COVID-19 symptoms (Pascolini et al, 2021;Stjepanovic et al, 2022;Son et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, studies that evaluated clinically significant antibodies associated with systemic rheumatic diseases (e.g. dsDNA, centromere, chromatin, ribosomal P, SSA-, SS-B, Sm, RNP, Scl-70, Jo-1) concluded that acute COVID-19 is not associated with a high prevalence of such autoantibodies [ [8] , [9] , [10] ]. Generally, studies on ANA in COVID-19 were small with differences in reported antibody levels and prevalence across studies without in-depth analysis of the nature of the autoantigens.…”
mentioning
confidence: 99%